Problem-Based Learning (PBL): An Innovation in Natural Sciences Studies to Improve Critical Thinking Skills - Winda Khoirotin Niswa; Agustiningsih Agustiningsih; Kendid Mahmudi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
The goal of this study was to see if students in class V Theme 6 could improve their critical thinking skills outcomes by using the Problem-Based Learning (PBL). This type of research is classroom action research using 2 cycles, namely, cycle I and cycle II, where each cycle consists of 2 meetings. The stages in the implementation of the PBL model are: 1) student orientation to the problem; 2) organizing students to learn; 3) guiding individual and group investigations; 4) developing and presenting the work; and 5) analyzing and evaluating the problem-solving process. Based on the results of data analysis, there is an average increase in classical critical thinking skills in the first cycle of 67.5 and the second cycle of 76.35. So it can be concluded that the Problem-Based Learning (PBL) can improve students' critical thinking skills outcomes